METODE PEMBELAJARAN TEAM TEACHING UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA PADA PEMINATAN EKONOMI - Yopi Nisa Febianti (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2022)
AbstractTeaching with the team teaching method is useful for providing varied teaching services to students, so that students can actively participate in learning activities. The research objective was to determine the increase in student learning activeness with the team teaching learning method in the Economic Specialization. This reseacrh used qualitative research methods. The results of the analysis show that the team teaching learning method has a good impact on increasing student learning activeness in the Economics Specialization, because students become more enthusiastic, diligent, active, and also critical when studying. The conclusion of this research is that with team teaching learning, students are enthusiastic and happy when learning because learning is carried out by two teachers, and added with different teaching methods, such as adding games when there is an interval of time.Keywords: Team teaching, student learning activeness, economic specialization.